Assessing the quality of service for drinking water supplies in rural settings: A synthetic index approach. (1st October 2019) - Molinos-Senante, María; Muñoz, Sebastián; Chamorro, Alondra
Abstract: In rural settings, the presence of water supply infrastructure does not guarantee that people will have access to dependable and high-quality drinking water. To evaluate deficiencies, an assessment of quality of service of rural drinking water supply systems (RDWSS) should be examined from a multi-criteria perspective, one that integrates economic, technical, administrative, and operational components of supplying water, which includes a variety of stakeholders to integrate their preferences in the development of a synthetic index. In this study, we followed a pioneering approach to evaluate the quality of service for RDWSS based on analytic hierarchy process (AHP) and Monte Carlo simulations. We empirically applied the approach to 40 RDWSS in Chile. The weights of a set of 14 performance indicators were allocated by representatives of the communities that manage the RDWSS and experts on technical and administrative issues revelling the different preferences of decision-makers. We found that there are significant differences in the quality of service provided by the RDWSS evaluated. The information provided by the synthetic indicator would be very helpful in supporting decision makers needing to prioritize investments among drinking water supplies in rural settings. Highlights: The quality of service of rural drinking water supply systems was evaluated. Uncertainty was considered in weights allocated to several criteria. Preferences of different decision-makers are significantly divergent. The age and size of the water system affects its quality of service.